2022
DOI: 10.3897/fr.25.80134
|View full text |Cite
|
Sign up to set email alerts
|

The first adult mantis lacewing from Baltic amber, with an evaluation of the post-Cretaceous loss of morphological diversity of raptorial appendages in Mantispidae

Abstract: Mantis lacewings (Neuroptera: Mantispidae) are prominent and charismatic predatory representatives of Insecta. Nevertheless, representatives of the group are surprisingly scarce in Paleogene deposits after a relative abundance of specimens known from Cretaceous. Here we present Mantispa? damzenogedanica sp. nov., representing the first adult of Mantispidae described from Baltic amber and the only Eocene adult mantispid hitherto preserved in amber. The new fossil species is also among the earliest representativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…This is not surprising, as former studies have indicated that Mesozoic representatives of Mantispidae were in certain aspects more derived than modern ones (e.g. Lu et al 2020;Shi et al 2020a, b;Baranov et al 2022a).…”
Section: The Femoral Morphology Of Mantis Lacewing Pupae In Compariso...mentioning
confidence: 78%
See 4 more Smart Citations
“…This is not surprising, as former studies have indicated that Mesozoic representatives of Mantispidae were in certain aspects more derived than modern ones (e.g. Lu et al 2020;Shi et al 2020a, b;Baranov et al 2022a).…”
Section: The Femoral Morphology Of Mantis Lacewing Pupae In Compariso...mentioning
confidence: 78%
“…For a quantitative comparison between adult stages and pupae, we used the data set from Baranov et al (2022a) and expanded it. We consider here all pupae known from groups that were traditionally considered as ingroups of Mantispidae (see below for details).…”
Section: Shape Analysismentioning
confidence: 99%
See 3 more Smart Citations